2001
DOI: 10.1097/00004647-200109000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Induces Changes in HIF-1 Target Genes in Neonatal Rat Brain

Abstract: Hypoxic preconditioning induces tolerance to hypoxic-ischemic injury in neonatal rat brain and is associated with changes in gene expression. Hypoxia-inducible factor-1 (HIF-1) is a transcription factor that is strongly induced by hypoxia or the hypoxia-mimetic compound cobalt chloride (CoCl(2)). Hypoxia-inducible factor-1 modulates the expression of several target genes including the glycolytic enzymes, glucose transporter-1 (GLUT-1), and erythropoietin. Recently, HIF-1 expression was shown to increase after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
164
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 45 publications
(109 reference statements)
6
164
0
1
Order By: Relevance
“…However, evidence suggest that cell-autonomous delayed apoptotic signaling plays a critical role in determining the ultimate burden of neuron loss after injury (Abe et al, 1995;Schwamm et al, 1998). Hypoxia is a potent stimulus for de novo gene expression, and sub-lethal hypoxic stress can enhance cell survival through the regulated expression of factors such as erythropoietin and vascular endothelial growth factor (Dirnagl et al, 2003;Jones and Bergeron, 2001). This process, also referred to as ischemic preconditioning, is supported in part by the activation of the hypoxia-inducible factor (HIF-1α) and an array of immediate early transcription factors with diverse biological functions including c-Jun and Egr-1/Krox-24 (Collaco-Moraes et al, 1994;Herdegen and Leah, 1998;Hsu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence suggest that cell-autonomous delayed apoptotic signaling plays a critical role in determining the ultimate burden of neuron loss after injury (Abe et al, 1995;Schwamm et al, 1998). Hypoxia is a potent stimulus for de novo gene expression, and sub-lethal hypoxic stress can enhance cell survival through the regulated expression of factors such as erythropoietin and vascular endothelial growth factor (Dirnagl et al, 2003;Jones and Bergeron, 2001). This process, also referred to as ischemic preconditioning, is supported in part by the activation of the hypoxia-inducible factor (HIF-1α) and an array of immediate early transcription factors with diverse biological functions including c-Jun and Egr-1/Krox-24 (Collaco-Moraes et al, 1994;Herdegen and Leah, 1998;Hsu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called tolerance. Ischemic tolerance can be achieved in brain by several preconditioning sublethal stresses such as hypoxia (1-3), ischemia itself (4), hypothermia (5), hyperthermia (6), hyperbaric oxygenation (7), metabolic inhibitors (8), spreading depression (9), as well as cytokines (10, 11).As hypoxic preconditioning is non-invasive and reproducible, this model has been used to study the mechanisms protecting the brain against hypoxia-ischemia particularly in newborn rats (3,(12)(13)(14). In addition, hypoxic preconditioning also induces tolerance against focal transient (15) and permanent (16) cerebral ischemia in adult mice.…”
mentioning
confidence: 99%
“…protects the brain against ischaemic injury, but the mechanisms were found to be different in both cases. These authors reported that hypoxic preconditioning is connected with the modulation of glucose transport and glycolysis by hypoxia and may contribute to the development of hypoxia-induced tolerance (12). In contrast, preconditioning with cobalt chloride did not produce any change in HIF-1 target gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…Jones and Bergeron (12) reported that prior exposure of newborn rats to 8% hypoxia or CoCl2 (60 mg/kg b.w.) protects the brain against ischaemic injury, but the mechanisms were found to be different in both cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation